New forms of cooperative learning in the classroom, foster attention of students attending higher education institutes - Flores Galarreta, Patricia Noelia (2019)
This descriptive study focuses on the student’s lack of attention during their learning process, whereby the key point is the student’s lack of motivation in the classroom. The five phases of the Design Thinking methodology and qualitative techniques such as interviewing and observation were applied. These tools were applied to students and teachers from two professional careers in two higher education institutes, with the aim of adapting our methodology towards new ways of classroom motivation, for them to build, from their own experience of the cooperative work of the students, their own knowledge with new forms of creative learning: the first, based on the visual stimulus that summarizes a lesson theme; the second, combining two stimuli: visual and auditory, illustrating the operational process of a learning theme. It is concluded that both proposals generate an interest to learn in the student, motivating his attention in the classroom.